Pengaruh Kecerdasan Emosional, Level Pendidikan, dan Optimisme terhadap Kebahagiaan pada Pelajar Sekolah Menengah - Dr. Nurul Hidayah, S.Psi., M.Si., Psikolog; Drs. Mujidin, M.Si., Ph.D; Husnul Khotimah Rustam Rustam Laoheng (Jurnal Evaluasi Pendidikan, 2021)
Happiness is a positive feeling. The purpose on this study is to know effect emotional intelligence, level of education, and optimism to happiness on students. Design study is purposive-quota sampling and google form. In this article, researcher using self-taught scale for 3 variable. Anacova was technique for analysis. There were 117 respondents who met the criteria with a composition of 36 junior high school and 81 senior high school. The results of the study described that there was no effect of EI, EL and optimism on happiness. The strength of each predictor was weak, but indicated that emotional intelligence and optimism correlate and even become an inseparable part of happiness.. Happiness was dynamic, dis not persist and change moods due to other factors that were not observed. Each individual could feel and evaluate happiness so that the value of happiness could not be generalized. Keywords: Emotional Intelligence, Education Level, Optimism, & Students.